KOMPETENSI PROFESIONAL GURU BAHASA DAN SASTRA INDONESIA - Nuryani Nuryani (BAHASTRA, 2018)
This paper will map out the professional competencies that Indonesian Language and Literature teachers must possess. The professional competence is mapped based on Permendiknas Attachment no. 16 of 2007 on the standard of Academic Qualification and Teacher Competence that is mastering material, structure, concepts, and intellectual mindset related subjects that taught. The competencies are spelled out in the following points: to understand the concepts, theories, and the linguistic material. Linguistic understandings related to the development of language learning materials, understanding the nature of language and language acquisition, understanding the position, function, and variety of Indonesian language, mastering the basics of Indonesian language as a reference to the use of Indonesian language is good and true, have the skills to speak Indonesian (listening, speaking , reading and writing). Meanwhile, literary understanding is related to understanding the theory and genre of Indonesian literature and able to appreciate the Indonesian literature receptively and productively.Â  Various competencies are expected to produce a professional teacher of Indonesian Language and Literature that makes learning Indonesian Language and Literature to be ideal.